Secondary battery and electronic device
By adding Mn elements to the positive electrode active material layer of the secondary battery, controlling the composition of lithium salts and adding specific compounds in the electrolyte, the problem of insufficient circulation and storage performance of the secondary battery is solved, and better circulation and rate performance are achieved.
Patent Information
- Application Number
- CN202510080242.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-22
AI Technical Summary
There are shortcomings in the circulation performance and storage performance of existing secondary batteries, especially in lithium-ion batteries, the corrosion problem of lithium bis(fluorosulfonyl)imide on the positive electrode current collector leads to a degradation of circulation performance.
By adding Mn elements to the positive electrode active material layer, controlling the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate in the electrolyte, and adding lithium difluorophosphate and sulfur-containing double bond compounds to the electrolyte, to reduce the impact of corrosion and improve battery performance.
It effectively reduces the corrosion effect of lithium bis(fluorosulfonyl)imide on the positive electrode current collector, improves the circulation and rate performance of the secondary battery, and allows it to better take into account storage performance and fast charging and discharging capabilities.
Smart Images

Figure BDA0005248565310000151 
Figure BDA0005248565310000161 
Figure BDA0005248565310000171
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electronic device. Background Art
[0002] Secondary batteries represented by lithium-ion batteries are widely used in digital electronic products, energy storage, drones, power tools, electric vehicles and other products due to their high energy density, long cycle life, high safety, fast charging capability and other characteristics. With the widespread application of secondary batteries, higher requirements are placed on the performance of secondary batteries, so it is necessary to provide a secondary battery with better cycle performance and storage performance. Summary of the invention
[0003] The present application provides a secondary battery and an electronic device, wherein the secondary battery has good cycle performance and storage performance.
[0004] In a first aspect, the present application provides a secondary battery comprising a positive electrode plate, a negative electrode plate and an electrolyte; wherein the positive electrode plate comprises a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises an Mn element, wherein the mass percentage of the Mn element is a% based on the mass of the positive electrode active material layer; the electrolyte comprises a lithium salt, the lithium salt comprises lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, and the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is b; a and b satisfy: 20≤a≤60; 0.003≤b / a≤1.
[0005] According to the present application, the lithium salt in the electrolyte includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate. Lithium bis(fluorosulfonyl)imide can effectively improve the rate performance of the secondary battery, but if the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is too high, corrosion will occur to the positive electrode collector, deteriorating the cycle performance of the secondary battery. By using a positive electrode active material containing the Mn element, the effect of lithium bis(fluorosulfonyl)imide on the positive electrode collector can be effectively reduced, and by controlling the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate in the lithium salt and the mass percentage of the Mn element in the positive electrode active material layer to meet the above conditions, the secondary battery can have good cycle performance and rate performance.
[0006] In some embodiments, the secondary battery satisfies at least one of the following conditions: (1) 0.2≤b≤40; preferably 0.5≤b≤32; (2) 0.01≤b / a≤0.6; (3) based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is 2% to 25%; preferably 3% to 20%. Based on the above embodiments, if at least one of the above conditions is met, the secondary battery has better cycle performance and / or rate performance.
[0007] In some embodiments, the electrolyte further includes lithium difluorophosphate, and the mass percentage of lithium difluorophosphate is c%, based on the mass of the electrolyte, and 0.001≤c≤1. Based on the above embodiment, further adding lithium difluorophosphate to the electrolyte can further inhibit the corrosion of the positive electrode current collector by the lithium salt in the electrolyte by forming a dense protective layer on the surface of the positive electrode current collector, thereby synergizing the lithium salt in the electrolyte with the Mn element in the positive electrode active material, and further improving the cycle performance and rate performance of the secondary battery. Preferably, 0.1≤c≤1.
[0008] In some embodiments, 0.2≤b / c≤20000. Based on the above embodiments, the mass percentage of lithium difluorophosphate and the mass ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate in the electrolyte are controlled to satisfy the above relationship, which can further improve the cycle performance and rate performance of the secondary battery. Preferably, 2≤b / c≤106.7.
[0009] In some embodiments, the positive electrode plate includes two or more positive electrode tabs disposed on one side of the positive electrode current collector, and the positive electrode tabs are sequentially distributed along the length direction of the positive electrode current collector; and / or the negative electrode plate includes a negative electrode current collector and two or more negative electrode tabs disposed on one side of the negative electrode current collector, and the negative electrode tabs are sequentially distributed along the length direction of the negative electrode current collector. Based on the above embodiments, the multi-tab structure of the lithium bis(fluorosulfonyl)imide cooperative electrode plate in the electrolyte can further improve the rate performance of the battery.
[0010] In some embodiments, the positive electrode active material further includes a metal element A, and the metal element A includes at least one of Ca, Na, Mg, Cr or Ti; based on the mass of the positive electrode active material layer, the mass percentage of the metal element A is 0.001% to 1%. Based on the above embodiment, the positive electrode active material includes the above elements, which can further reduce the effect of lithium bis(fluorosulfonyl)imide on the positive electrode current collector and improve the cycle performance of the secondary battery.
[0011] In some embodiments, the electrolyte further includes a sulfur-oxygen double bond compound; the sulfur-oxygen double bond compound is selected from at least one of methane disulfonic acid methylene ester, 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 1,3-propane disulfonic anhydride, 2-methylbutane sultone or 1,3-propylene glycol cyclic sulfate; based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.01% to 5%. Based on the above embodiment, further adding a sulfur-oxygen double bond compound to the electrolyte and controlling the mass percentage within the above range can further inhibit the corrosion of the lithium salt in the electrolyte to the positive electrode current collector, so that the secondary battery has better rate performance and cycle performance.
[0012] In some embodiments, the positive electrode active material includes at least one of lithium manganate, lithium nickel manganate, lithium nickel cobalt manganate, lithium manganese phosphate, lithium iron manganese phosphate, or lithium-rich manganese-based materials. Based on the above embodiments, the use of the above types of positive electrode active materials can reduce the impact of lithium bis(fluorosulfonyl)imide on the positive electrode current collector and improve the cycle performance of the secondary battery.
[0013] In some embodiments, the electrolyte further comprises a cyclic carbonate compound, the cyclic carbonate compound comprises at least one of ethylene carbonate and propylene carbonate, and the mass percentage of the cyclic carbonate compound is 5% to 40% based on the mass of the electrolyte. Based on the above embodiment, the electrolyte comprising the cyclic carbonate in the above mass percentage can improve the stability of lithium bis(fluorosulfonyl)imide, reduce its influence on the positive electrode current collector, and improve the ion transmission efficiency, thereby improving the rate performance and cycle performance of the secondary battery.
[0014] In a second aspect, the present application provides an electronic device, comprising a secondary battery according to any embodiment of the first aspect.
[0015] According to the present application, since the electronic device includes the secondary battery described in any embodiment of the first aspect, it has the beneficial effects of the first aspect. DETAILED DESCRIPTION
[0016] The various embodiments or implementation schemes in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments.
[0017] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.
[0018] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0019] In the present application, the battery may include a lithium-ion secondary battery, a lithium-ion primary battery, a lithium-sulfur battery, a sodium-lithium-ion battery, a sodium-ion battery or a magnesium-ion battery, etc., and the embodiments of the present application do not limit this. The battery may be cylindrical, flat, rectangular or other shapes, etc., and the embodiments of the present application do not limit this.
[0020] Secondary battery
[0021] In a first aspect, the present application provides a secondary battery comprising a positive electrode plate, a negative electrode plate and an electrolyte; wherein the positive electrode plate comprises a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises an Mn element, wherein the mass percentage of the Mn element is a% based on the mass of the positive electrode active material layer; the electrolyte comprises a lithium salt, the lithium salt comprises lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, and the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is b; a and b satisfy: 20≤a≤60; 0.003≤b / a≤1.
[0022] According to the present application, the lithium salt in the electrolyte includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate. Lithium bis(fluorosulfonyl)imide can effectively improve the rate performance of the secondary battery, but if the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is too high, corrosion will occur to the positive electrode collector, deteriorating the cycle performance of the secondary battery. By using a positive electrode active material containing the Mn element, the effect of lithium bis(fluorosulfonyl)imide on the positive electrode collector can be effectively reduced, and by controlling the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate in the lithium salt and the mass percentage of the Mn element in the positive electrode active material layer to meet the above conditions, the secondary battery can have good cycle performance and rate performance.
[0023] Specifically, lithium bis(fluorosulfonyl)imide in the electrolyte is easily dissociated into lithium ions and bis(fluorosulfonyl)imide ions in the solvent due to its small molecule and strong ion dissociation ability, which can significantly improve the ionic conductivity of the electrolyte. However, bis(fluorosulfonyl)imide ions are easily decomposed at higher voltages to produce corrosive by-products (such as hydrogen fluoride, etc.), and the positive electrode collector is generally aluminum foil. The corrosive by-products have a strong corrosive effect on the positive electrode collector, causing the positive electrode collector to become thinner and the surface to oxidize, resulting in poor contact between it and the positive electrode active material layer, thereby reducing the effective utilization rate of the active material, and during the charge and discharge process, the active material gradually fails to have good contact with the positive electrode collector, resulting in a gradual decline in capacity, which reduces the overall performance of the secondary battery (especially the cycle performance). The present application reduces the concentration of bis(fluorosulfonyl)imide ions by mixing lithium bis(fluorosulfonyl)imide with lithium hexafluorophosphate as lithium salts, and uses a positive electrode active material including the Mn element. The Mn element has a certain influence on the voltage platform of the battery. Generally, when the Mn element content is high, the operating voltage platform of the battery will be reduced, which can reduce the decomposition of the bis(fluorosulfonyl)imide ions. At the same time, the Mn element can also improve the stability of the electrolyte, reduce the side reaction between the electrolyte and the positive electrode active material, and thus reduce the influence of lithium bis(fluorosulfonyl)imide on the positive electrode current collector; wherein the mass percentage a of the Mn element in the positive electrode active material layer and the mass ratio b of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate meet the following conditions: 20≤a≤60; 0.003≤b / a≤1, and the secondary battery can better balance the cycle performance and rate performance.
[0024] It can be understood that if the a value is too small, the effect of lowering the battery operating voltage platform and reducing the side reactions between the electrolyte and the positive electrode active material is not obvious, and the influence of lithium bis(fluorosulfonyl)imide in the electrolyte on the positive electrode current collector cannot be effectively reduced. If the a value is too high, it will have an adverse effect on the energy density and rate performance of the secondary battery; if the b / a value is too small, the rate performance of the secondary battery cannot be significantly improved. If the b / a value is too large, the influence of lithium bis(fluorosulfonyl)imide on the positive electrode current collector is relatively large, which will affect the comprehensive performance of the secondary battery. For example, the value of a can be 20, 21.3, 24.0, 27.0, 31.1, 32.8, 38.3, 38.8, 44.1, 47.6, 49.7, 53.8, 54.9, 59.8, 60, or a range formed by any of the above values; the value of b / a can be 0.003, 0.043, 0.098, 0.178, 0.280, 0.313, 0.434, 0.469, 0.592, 0.640, 0.713, 0.799, 0.847, 0.963, 1, or a range formed by any of the above values.
[0025] In some embodiments, 0.01≤b / a≤0.6. Based on the above embodiments, when b / a is within the above range, the secondary battery can better balance the cycle performance and rate performance.
[0026] In some embodiments, 0.2≤b≤40. Based on the above embodiments, when b is within the above range, the rate performance of the secondary battery is better. For example, the value of b can be 0.2, 0.5, 3.8, 6.9, 10.1, 14.3, 18.6, 21.1, 23.8, 25.8, 28.4, 33.5, 34.7, 38.4, 40, or within the range of any of the above values; preferably 0.5≤b≤32.
[0027] In some embodiments, based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is 1% to 25%. For example, based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide can be 1%, 1.6%, 2.8%, 3%, 4.2%, 5.0%, 6.9%, 7.6%, 8.5%, 10.7%, 12.0%, 13.3%, 14.0%, 15.0%, 16.7%, 17.9%, 19.4%, 20%, 21.5%, 23.6%, 24.3%, 25%, or within the range of any of the above values; preferably 3% to 20%.
[0028] In some embodiments, the electrolyte further includes lithium difluorophosphate, and the mass percentage of the lithium difluorophosphate is c%, based on the mass of the electrolyte, and 0.001≤c≤1.
[0029] Based on the above embodiment, lithium difluorophosphate is further added to the electrolyte. Lithium difluorophosphate can further inhibit the corrosion of the positive electrode collector by the lithium salt in the electrolyte by forming a dense protective layer on the surface of the positive electrode collector, thereby coordinating the lithium salt in the electrolyte with the Mn element in the positive electrode active material to further improve the cycle performance and rate performance of the secondary battery. For example, the value of c can be 0.001, 0.006, 0.154, 0.178, 0.302, 0.350, 0.398, 0.510, 0.612, 0.678, 0.693, 0.832, 0.917, 0.963, 1, or within the range of any of the above values. Preferably, 0.1≤c≤1.
[0030] In some embodiments, 0.2≤b / c≤20000. Based on the above embodiments, the mass percentage of lithium difluorophosphate and the mass ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate in the electrolyte are controlled to satisfy the above relationship, which can further improve the cycle performance and rate performance of the secondary battery. For example, the value of b / c can be 0.2, 904.0, 2842.6, 3795.4, 5424.9, 6588.8, 7923.0, 10268.1, 10780.9, 13135.9, 14107.8, 15787.7, 18144.5, 19095.5, 20000, or within the range of any of the above values. Preferably, 2≤b / c≤106.7.
[0031] In some embodiments, the positive electrode plate includes two or more positive electrode tabs disposed on one side of the positive electrode current collector, and the positive electrode tabs are sequentially distributed along the length direction of the positive electrode current collector; and / or the negative electrode plate includes a negative electrode current collector and two or more negative electrode tabs disposed on one side of the negative electrode current collector, and the negative electrode tabs are sequentially distributed along the length direction of the negative electrode current collector. Based on the above embodiments, the multi-tab structure of the lithium bis(fluorosulfonyl)imide cooperative electrode plate in the electrolyte can further improve the rate performance of the battery.
[0032] In some embodiments, the positive electrode active material further includes metal element A, which includes at least one of Ca, Na, Mg, Cr or Ti; based on the mass of the positive electrode active material layer, the mass percentage of metal element A is 0.001% to 1%.
[0033] Based on the above embodiments, the positive electrode active material includes the above elements, which can further reduce the influence of lithium bis(fluorosulfonyl)imide on the positive electrode current collector and improve the cycle performance of the secondary battery. For example, based on the mass of the positive electrode active material layer, the mass percentage of the metal element A can be 0.001%, 0.049%, 0.128%, 0.179%, 0.233%, 0.366%, 0.391%, 0.494%, 0.602%, 0.690%, 0.754%, 0.804%, 0.881%, 0.940%, 1%, or within the range of any of the above values.
[0034] In some embodiments, the electrolyte further includes a sulfur-oxygen double bond compound; the sulfur-oxygen double bond compound is selected from at least one of methane disulfonic acid methylene ester, 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 1,3-propane disulfonic anhydride, 2-methylbutane sultone or 1,3-propylene glycol cyclic sulfate; based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.01% to 5%. Based on the above embodiment, further adding a sulfur-oxygen double bond compound to the electrolyte and controlling the mass percentage within the above range can further inhibit the corrosion of the lithium salt in the electrolyte to the positive electrode current collector, so that the secondary battery has better rate performance and cycle performance. For example, the mass percentage of the sulfur-oxygen double bond compound can be 0.01%, 0.17%, 0.57%, 0.83%, 1.41%, 1.65%, 1.96%, 2.60%, 2.97%, 3.28%, 3.68%, 4.06%, 4.28%, 4.86%, 5%, or any range composed of the above values.
[0035] In some embodiments, the positive electrode active material includes at least one of lithium manganate, lithium nickel manganate, lithium nickel cobalt manganate, lithium manganese phosphate, lithium iron manganese phosphate, or lithium-rich manganese-based materials. Based on the above embodiments, the use of the above types of positive electrode active materials can reduce the impact of lithium bis(fluorosulfonyl)imide on the positive electrode current collector and improve the cycle performance of the secondary battery.
[0036] In some embodiments, the electrolyte further comprises a cyclic carbonate compound, the cyclic carbonate compound comprises at least one of ethylene carbonate (EC) and propylene carbonate (PC), and the mass percentage of the cyclic carbonate compound is 5% to 40% based on the mass of the electrolyte. Based on the above embodiment, the electrolyte comprising the cyclic carbonate in the above mass percentage can improve the stability of lithium bis(fluorosulfonyl)imide, reduce its influence on the positive electrode current collector, and improve the ion transmission efficiency, thereby improving the rate performance and cycle performance of the secondary battery.
[0037] In some embodiments, the electrolyte further includes at least one of ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0038] In some embodiments, the positive electrode active material layer includes a positive electrode conductive material; the type of the positive electrode conductive material is not limited, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.
[0039] In some embodiments, the positive electrode active material layer includes a positive electrode binder. The type of the positive electrode binder is not particularly limited, and in the case of a coating method, it can be any material that is soluble or dispersible in a liquid medium used in electrode manufacturing. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose or nitrocellulose; rubber-like polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber or ethylene-propylene rubber; thermoplastic elastomer-like polymers such as styrene-butadiene-styrene block copolymer or its hydride, ethylene-propylene-diene terpolymer (EPDM), styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer or its hydride; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer or propylene-α-olefin copolymer; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride or polytetrafluoroethylene-ethylene copolymer; polymer compositions having ionic conductivity of alkali metal ions, etc. The above positive electrode binders may be used alone or in any combination.
[0040] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; non-protonic polar solvents such as hexamethylphosphoramide or dimethyl sulfoxide, etc.
[0041] There is no particular limitation on the type of positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium or tantalum; materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0042] The thickener is usually used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch or casein and their salts, etc. The above thickeners may be used alone or in any combination.
[0043]
Negative electrode
[0044] The secondary battery also includes a negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.
[0045] The negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), silicon, silicon-carbon composites, SiO x (0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. Optionally, the negative electrode active material may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide or calcined coke, etc.
[0046] The negative electrode active material layer of the present application also includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the manufacture of the electrolyte or electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.
[0047] The negative electrode active material layer of the present application also includes a conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0048] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode active layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode active layer is 30μm to 160μm. In the present application, the negative electrode active layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.
[0049] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode plate, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode plate can be 3 tons to 30 tons.
[0050] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.
[0051]
Isolation film
[0052] In the present application, a separator is usually provided between the positive electrode sheet and the negative electrode sheet. The separator is used to separate the positive electrode sheet and the negative electrode sheet, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.
[0053] The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of isolation membrane may include at least one of woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.
[0054] In the present application, the isolation membrane may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0055] The pore size of the isolation membrane in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the isolation membrane is greater than 5 μm or greater than 8 μm. In some embodiments, the thickness of the isolation membrane is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the isolation membrane is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.
[0056] The electrochemical device of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the electrochemical device, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0057] Electronic devices
[0058] In a second aspect, the present application provides an electronic device, comprising a secondary battery according to any embodiment of the first aspect.
[0059] According to the present application, since the electronic device includes the secondary battery of any embodiment of the first aspect, it has the beneficial effects of the first aspect.
[0060] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0061] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0062] <Test method>
[0063] (1) Test of Al content on negative electrode after storage:
[0064] Place the lithium-ion battery in a constant temperature box at 25°C, let it stand for 30 minutes, charge it to 4.2V at a constant current rate of 1C, then charge it at constant voltage until the current is less than or equal to 0.05C, then let it stand for 5 minutes, discharge it to 2.8V at a constant current rate of 1C, then charge it to 4.2V at a constant current rate of 1C, charge it at constant voltage until the current is less than or equal to 0.05C, and then place the fully charged lithium-ion battery in a 60°C oven for storage for 90 days.
[0065] The stored lithium-ion batteries are disassembled to obtain negative electrode sheets. Any position of the negative electrode sheets is randomly selected to obtain negative electrode sheets of a certain size. The negative electrode sheets are digested with acid to form a solution. The solution is atomized and then subjected to inductively coupled plasma (ICP) testing to obtain the content of Al element in the negative electrode active material.
[0066] (2) Rate performance test:
[0067] Place the lithium-ion battery in a 25°C constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 1C to a voltage of 4.2V, and then charge it at a constant voltage of 4.2V to a current of less than or equal to 0.05C. Subsequently, discharge it at a constant current of 1C and 5C to 2.8V, respectively, to obtain the 1C discharge capacity and 5C discharge capacity of the lithium-ion battery. Divide the 5C discharge capacity by the 1C discharge capacity to obtain the 5C capacity retention rate.
[0068] Example 1
[0069] (1) Preparation of negative electrode: Mix the negative electrode active material artificial graphite, the conductive agent Super P, and the negative electrode binder sodium carboxymethyl cellulose in a mass ratio of 96:2:2, add deionized water and stir evenly to obtain a negative electrode slurry with a solid content of 70wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and then dried at 110°C. The above steps are repeated on the other surface of the negative electrode current collector. After cold pressing, a double-sided coated negative electrode sheet with a single-sided negative electrode material layer thickness of 150μm is obtained. The compaction density of the single-sided negative electrode material layer is 1.6g / cm 3 Then the negative electrode sheet is die-cut into a negative electrode sheet with two or more negative electrode tabs on one side of the negative electrode collector and a specification of 78mm×875mm.
[0070] (2) Preparation of positive electrode: Lithium manganese iron phosphate (LiMn 0.6 Fe 0.4 PO4), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added as a solvent. The system is stirred under the action of a vacuum mixer until the system becomes a uniform positive electrode slurry with a solid content of 75wt%. The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12μm, wherein the mass percentage of Mn element in the positive electrode active material layer a%, the type of metal element A and the mass percentage of the positive electrode active material layer are shown in Table 1; dried at 85°C, and the above steps are repeated on the other surface of the positive electrode current collector. After cold pressing, a double-sided coated positive electrode sheet with a thickness of 100μm is obtained. The positive electrode sheet is die-cut into a positive electrode sheet with two or more positive electrode tabs on one side of the positive electrode current collector and a specification of 74mm×867mm.
[0071] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10ppm, the cyclic carbonate compound EC and DEC are uniformly mixed to obtain a base solvent. The fully dried lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium difluorophosphate, sulfur-oxygen double bond compound and cyclic carbonate are dissolved in the above base solvent and stirred evenly. Among them, based on the mass of the electrolyte, the mass percentage of EC is 20%, the mass percentage of lithium bis(fluorosulfonyl)imide is 12%, the mass percentage of lithium hexafluorophosphate is 0.6%, the mass percentage of 1,3-propane sultone is 1%, and the remainder is supplemented by the component DEC.
[0072] (4) Preparation of isolation membrane: A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0073] (5) Preparation of lithium-ion battery: The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, placed in a vacuum oven at 85°C to dry for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, shaping, capacity testing, secondary packaging and other processes, a lithium-ion battery is obtained.
[0074] The Al content of the negative electrode and the rate performance test were performed on the lithium-ion battery after storage. The results are shown in Table 1.
[0075] Examples 2 to 37, Comparative Example 1
[0076] Except for adjusting the parameters according to Table 1, the rest is the same as Example 1.
[0077] The Al element content on the negative electrode and the rate performance test were performed on the above lithium-ion batteries after storage. The results are shown in Table 1.
[0078]
[0079]
[0080]
[0081]
[0082] According to the embodiments in Table 1, compared with Comparative Example 1, the Al element content on the negative electrode after storage is lower and the 5C capacity retention rate is higher, wherein the Al element content on the negative electrode after storage is derived from the corrosion of the positive electrode current collector by the electrolyte, and the lower the Al element content, the smaller the degree of corrosion of the positive electrode current collector, and the better the cycle performance of the corresponding battery. A higher 5C capacity retention rate indicates that the rate performance of the battery is better, that is, by controlling the mass percentage of the Mn element in the positive electrode active material layer and controlling the composition of the lithium salt in the electrolyte, and satisfying the conditions of 20≤a≤60; 0.003≤b / a≤1, the battery has better cycle performance and rate performance.
[0083] According to Examples 1 to 15, under the condition of 0.01≤b / a≤0.6, the battery can better balance the cycle performance and the rate performance; under the condition of 0.5≤b≤32, the battery can better balance the cycle performance and the rate performance; when the mass percentage of lithium bis(fluorosulfonyl)imide in the electrolyte is 3% to 20%, the battery can better balance the cycle performance and the rate performance.
[0084] According to Examples 1, 7, 10 to 21, further adding lithium difluorophosphate to the electrolyte can cooperate with the Mn element and lithium salt in the positive electrode active material to further improve the cycle performance and rate performance of the battery; and under the conditions of 2≤b / c≤106.7 and / or 0.1≤c≤1, the cycle performance and rate performance of the battery are better.
[0085] According to Examples 7, 22 to 28, doping the positive electrode active material with metal element A and controlling the mass percentage of metal element A in the positive electrode active material layer to be between 0.001% and 1% can further improve the cycle performance and rate performance of the battery.
[0086] According to Examples 7, 29 to 33, further adding a sulfur-oxygen double bond compound into the electrolyte and controlling its mass percentage in the electrolyte to be between 0.01% and 5% can further improve the cycle performance and rate performance of the battery.
[0087] According to Examples 7, 34 to 37, it can be seen that the electrolyte includes 5% to 40% by mass of the cyclic carbonate compound, and the battery has good cycle performance and rate performance.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A secondary battery, characterized in that: Including positive electrode sheet, negative electrode sheet and electrolyte; The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a Mn element, wherein the mass percentage of the Mn element is a% based on the mass of the positive electrode active material layer; The electrolyte includes a lithium salt, wherein the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, and the mass ratio of the lithium bis(fluorosulfonyl)imide to the lithium hexafluorophosphate is b; The a and b satisfy: 20≤a≤60; 0.003≤b / a≤1.
2. The secondary battery according to claim 1, characterized in that: The secondary battery satisfies at least one of the following conditions: (1)0.2≤b≤40; (2) 0.01≤b / a≤0.6; (3) Based on the mass of the electrolyte, the mass percentage of the lithium bis(fluorosulfonyl)imide is 2% to 25%.
3. The secondary battery according to claim 1 or 2, characterized in that: The electrolyte further comprises lithium difluorophosphate. Based on the mass of the electrolyte, the mass percentage of the lithium difluorophosphate is c%, and 0.001≤c≤1.
4. The secondary battery according to claim 3, characterized in that: 0.2≤b / c≤20000.
5. The secondary battery according to claim 1, characterized in that: The positive electrode sheet comprises two or more positive electrode tabs arranged on one side of the positive electrode current collector, and the positive electrode tabs are sequentially distributed along the length direction of the positive electrode current collector; and / or The negative electrode sheet includes a negative electrode current collector and two or more negative electrode tabs arranged on one side of the negative electrode current collector, and the negative electrode tabs are distributed in sequence along the length direction of the negative electrode current collector.
6. The secondary battery according to claim 1, characterized in that: The positive electrode active material further includes a metal element A, and the metal element A includes at least one of Ca, Na, Mg, Cr or Ti; based on the mass of the positive electrode active material layer, the mass percentage of the metal element A is 0.001% to 1%.
7. The secondary battery according to claim 1, characterized in that: The electrolyte further comprises a sulfur-oxygen double bond compound; the sulfur-oxygen double bond compound is selected from at least one of methanedisulfonic acid methylene ester, 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 1,3-propanedisulfonic anhydride, 2-methylbutane sultone or 1,3-propylene glycol cyclic sulfate; Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.01% to 5%.
8. The secondary battery according to claim 1, characterized in that: The positive electrode active material includes at least one of lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium manganese phosphate, lithium manganese iron phosphate or lithium-rich manganese-based materials.
9. The secondary battery according to claim 1, characterized in that: The electrolyte further comprises a cyclic carbonate compound, wherein the cyclic carbonate compound comprises at least one of ethylene carbonate and propylene carbonate, and the mass percentage of the cyclic carbonate compound is 5% to 40% based on the mass of the electrolyte.
10. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.